Dynamic evolutionary game model for coal mine safety monitoring and control and its application - Ruxiang QIN; Tao SHEN; Shihui LI (Meikuang Anquan)
To enhance the practical application of the coal mine safety monitoring and control system, by constructing a dynamic evolutionary game model, the dynamic game trend between the users of the monitoring and control system and the monitored objects is analyzed. The model takes the strategy changes of the two major subjects as the core, explores the influence of parameter changes on the strategy trend and its convergence state, and proposes the inspection method and reward and punishment system for optimizing monitoring and control. The model parameters were adjusted and optimized in combination with previous studies, and the transformation coefficient was calculated through practical applications, thereby verifying the parameters of the game model. Ultimately, the game model was practiced and promoted in aspects such as formulating safety goals, solving the problem of information asymmetry, evaluating safety detection and monitoring work, and formulating detailed rules of safety detection strategies. The research finds that both sides of the game exhibit the characteristic of “dynamic infection”, that is, the strategy change of one side will cause the strategy adjustment of the other side. Meanwhile, among the two sides of the game, one side is the active side and the other side is the passive side. The different extreme strategies of the active side (y≤0.1 or y≥0.9) can completely affect the passive side over time, while the extreme strategies of the passive side have an incomplete impact on the active side; furthermore, the increase of the “full cooperation” parameters J and d will promote the convergence of the two main strategies to 1, indicating that a higher initial intention accelerates the convergence process; when the “negative return” parameter j decreases by 50% and the “positive return” parameter b increases by 50%, the implementation of monitoring and control work is enhanced. However, when the b value drops by more than the threshold (3.42%), monitoring and control personnel may turn to inadequate work. The study results provide quantitative analysis tools for coal mining enterprises to formulate safety monitoring and control strategies suitable for their own conditions, thereby helping to improve the operational efficiency of the system and the safety management level of the enterprise. By optimizing parameters and adjusting strategies, it is expected that the coal mine safety monitoring and control system can serve the safe production of coal mines more effectively, reduce the occurrence of accidents, and ensure the life safety of miners.